2021
DOI: 10.1590/1678-4685-gmb-2020-0138
|View full text |Cite
|
Sign up to set email alerts
|

Updated birth prevalence and relative frequency of mucopolysaccharidoses across Brazilian regions

Abstract: The mucopolysaccharidoses (MPS) are a group of lysosomal storage disorders caused by 11 enzyme deficiencies, classified into seven types. Data on the birth prevalence of each MPS type are available for only a few countries, and the totality of cases may be underestimated. To determine the epidemiological profile of MPS in each Brazilian region, we analyzed data collected between 1982 and 2019 by a national reference laboratory and identified 1,652 patients. Using data between 1994 and 2018, the birth prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…MPS II is the most frequent type of MPS in Brazil (Josahkian et al, 2021), the same occurring in some Asian countries such as Japan, South Korea, Taiwan, and China, as well as in a few European countries, as Switzerland and Estonia (Khan et al, 2017), and Israel (Schaap & Bach, 1980).…”
Section: According To Human Gene Mutation Database (Hgmd-the Humanmentioning
confidence: 99%
“…MPS II is the most frequent type of MPS in Brazil (Josahkian et al, 2021), the same occurring in some Asian countries such as Japan, South Korea, Taiwan, and China, as well as in a few European countries, as Switzerland and Estonia (Khan et al, 2017), and Israel (Schaap & Bach, 1980).…”
Section: According To Human Gene Mutation Database (Hgmd-the Humanmentioning
confidence: 99%
“…MPS III is the most common in Germany, Netherlands, and Emirates (Al-Jasmi et al, 2013). MPS II is more frequent in Brazil (Josahkian et al, 2021), China, and Japan (Chen et al, 2016;Khan et al, 2017) while Canada (Lowry et al, 1990) and Columbia (Moreno-Giranldo et al, 2020) reported MPS IV and Arab (Moammar et al, 2010) reported MPS VI as the rst condition.…”
Section: Discussionmentioning
confidence: 99%
“…MPS III is the most common in Germany, Netherlands 4 , and Emirates 36 . MPS II is more frequent in Brazil 37 , China, and Japan 38,39 while Canada 35 and Columbia 12 reported MPS IV and Arab 40 reported MPS VI as the rst condition.…”
Section: Discussionmentioning
confidence: 99%